Pengaruh Terapi Okupasi Terhadap Kemampuan Mengontrol Halusinasi Pada Pasien Gangguan Jiwa di Rumah Sakit Jiwa Prof. Dr. V.L. Ratumbuysang Minahasa - Natasya Alya Bilondatu; Sri Wahyuni; Helly Katuuk (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2023)
Mental disorders are disorders in the mind, behavior, and mood of feelings characterized in the form of a set of symptoms or changes. Hallucinations are one of the symptoms of mental disorders where clients experience sensory changes in perception, feeling sensations in the form of hearing, sight, taste, touch, or smell. This research uses the research method "Pre-Experiment Design with One Group Pre-Post Test Design approach. The sample was taken based on the number of respondents as many as 16 people using purposive sampling. Data collection is carried out by means of interviews and filling out questionnaires. Furthermore, the data collected was processed by researchers using the help of the SPSS Version 16.0 computer program to be analyzed using the Paired T Test with a significance level (α) of 0.05 The results showed that there were respondents with the ability to control hallucinations before or after being given occupational therapy showed changes for the better. Judging from the average ability to control pre-test hallucinations which is 1.13 or in the incapable category and the average ability to control hallucinations post test is 1.81 or is in the capable category and there is a difference of 668 which shows that there is a difference in the ability to control pre and post hallucinations where the ability to control hallucinations occurs. The conclusion in this study is the effect of occupational therapy on the ability to control hallucinations in mental patients at the mental hospital Prof. Dr. V.L. Ratumbuysang Minahasa. Suggestions for the results of this study to be a reference for readers.